Impact of recovery strategies on physiological and performance parameters in karate athletes: a randomized crossover study - Martínez-Rodríguez, A.; López-Plaza, D.; Nadal-Nicolás, Y.; Sánchez-Sánchez, J.; Leyva-Vela, B.; Cuestas-Calero, B.; Ramos-Campo, D.; Andreu-Caravaca, L.; Rubio-Arias, J. (Sport Sciences for Health, 2025)
Purpose Karate training and competition are characterized by high intensity efforts with short recovery periods that typically cause muscle fatigue and functional capacity impairments. This study aimed to examine the effects of different recovery strategies on physiological, tensiomyographic, and physical fitness parameters at pre, post, 0 h, 24 h, 48 h and 72 h after a high-demanding Karate Specific Aerobic Test (KSAT).